Structure, Distribution, and Spatial Patterns of Epiphytic Orchids (Orchidaceae) at Coastal Forest of the Sempu Island Nature Reserve, Malang, East Java - Asep Sadili (Jurnal Ilmu Kehutanan)
The aim of this study is to know the structure, spatial pattern, and distribution of epiphytic orchids in coastal forest Sempu Nature Reserve, Malang, East Java. This study used an elongated plot of 10 m x 1.000 m (1 ha), and was divided into 100 subplots. The location of plot was from Semut Beach to the direction of Sumber Air Tawar Beach. All the epiphytic orchids species of inside plot were recorded and counted (clumps). The results showed that there was four species from three genera with density of 77 clumps/ha. The most dominant species was Taeniophyllum cf. biocellatum, followed by Dendrobium subulatum, Grosourdya appendiculata, and Dendrobium crumenatum. Spatial pattern of distribution based on three parameter indices, and chi-square test showed that every species showed a random pattern.